2022
DOI: 10.3390/polym14020296
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Tensile Strength of the Fabrics Used in Firefighters’ Bunker Gear under Radiant Heat Exposure

Abstract: More than 60,000 firefighters’ injuries were reported by the National Fire Protection Association in the U.S. in 2019. Inadequate protection by bunker gear could be a reason for most of the injuries. Firefighters repeatedly encounter thermal hazards due to their job responsibilities. Degradation could occur on bunker gear fabric during thermal exposure. It has been found that the presence of moisture affects performance as well, which may come from wearers’ sweat. Proper evaluation of the tensile strength of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…49,50 Some of firefighting garments have shown to lose their strength even at lower heat flux of 10 kW m --2 . 9 McCarthy and Di Marzo 47 also observed that with intense heat flux (20 kW m --2 ) firefighter protective gear experiences degradation even at extreme short durations as 30-second exposure. However, aramid fibres, which are the main material for bunker gear, are reported to start failing to provide thermal protection when exposed to 600–800°C due to their decomposition behaviour.…”
Section: Firefighter’s Thermal Exposurementioning
confidence: 95%
See 3 more Smart Citations
“…49,50 Some of firefighting garments have shown to lose their strength even at lower heat flux of 10 kW m --2 . 9 McCarthy and Di Marzo 47 also observed that with intense heat flux (20 kW m --2 ) firefighter protective gear experiences degradation even at extreme short durations as 30-second exposure. However, aramid fibres, which are the main material for bunker gear, are reported to start failing to provide thermal protection when exposed to 600–800°C due to their decomposition behaviour.…”
Section: Firefighter’s Thermal Exposurementioning
confidence: 95%
“…9,16 The multi-layer system is designed to increase the overall thickness and consequently improves the protection against low-level radiant heat exposure. 9,18 Firefighter protective clothing has recently received growing attention because of the extreme thermal exposures commonly exposed to and the need to provide firefighters protection in those conditions.…”
Section: Bunker Gearmentioning
confidence: 99%
See 2 more Smart Citations
“…Injuries caused due to the thermal and thermo-physiological comfort hazards during the firefighting are common among the firefighters (Mandal et al, 2021;Mazumder, 2021;Mazumder et al, 2022). In addition to thermal and thermo-physiological comfort hazards, exposure to harmful chemicals that may contribute to the increased cancer risk has become an increasing concern in the firefighting community (Trowbridge et al, 2020;Muensterman et al, 2021).…”
Section: Introductionmentioning
confidence: 99%